Evaluating the eco-innovation strategy in business opportunity identification - enterprise business growth nexus. (28th May 2020) - Amara, Dhekra Ben; Hong, Chen; Hafeez, Muhammad
Although the eco-innovation phenomenon concerning green growth has received increasing attention over the past several years, methodological and theoretical approaches for investigating this phenomenon are poorly developed. Against this context, this research analyses the relationship between business opportunity identification factors and enterprises' sustainable business growth by exploring the mediating effect of eco-innovation strategy. Using data from Tunisian agricultural and agri-food enterprises, we chose a Structural equation modelling to assess the relationships among variables. According to statistical results: 1) business opportunity identification factors are positively associated with eco-innovation strategy and enterprises' sustainable business growth; 2) eco-innovation strategy has positive relationship with enterprises' sustainable business growth; 3) eco-innovation strategy mediates the relationship between business opportunity identification factors and enterprises' sustainable business growth, which serves as an innovative behaviour for entrepreneurs to make some profits. We provide suggestions for the future in the area of sustainable development and entrepreneurship.